Clinical outcomes of robotic-assisted laparoscopic partial nephrectomy with renal hypothermia perfusion by renal artery balloon catheter in treating patients with complex renal tumors - Bai, YuChen; Yang, YunKai; Wei, HaiBin; Quan, Jing; Wei, Fei; Zhang, Qi; Liu, Feng (Frontiers in Oncology, 2022)
Objective This study aimed to investigate the safety and efficacy of renal hypothermic perfusion by renal artery balloon catheter during robot-assisted laparoscopic partial nephrectomy (P-RALPN) for patients with complex renal tumors. Materials and methods We retrospectively identified 45 patients with complex renal tumors who received standard robot-assisted laparoscopic partial nephrectomy (S-RALPN) and 11 patients treated with P-RALPN from September 2017 to October 2021. Preoperative patients’ characteristics and intraoperative surgical parameters including operating time, blood loss, hospitalization, pre- and post-surgical glomerular filtration rate (GFR), and postoperative survival time were collected and compared between the two groups. The patients’ body temperature, real-time kidney temperature, and short-term renal function were analyzed in the P-RALPN group. Results There was no statistically significant difference on median intraoperative estimated blood loss and postoperative hospitalization between the two groups. Patients who received P-RALPN had a slightly longer operative time than those who received S-RALPN (103.1 versus 125.9; p = 0.09). In the P-RALPN group, the volume of perfusion solution was 533.2 ml (range, 255.0–750.0 ml), the median temperature of kidney was 22.6°C (range, 21.7–24.1°C) after the kidney cools down, and the median minimum intraoperative temperature of patients was 36.1°C (range 35.2–36.7°C). The ischemia time in the S-RALPN group was markedly lower than that in the P-RALPN group (21.5 versus 34.8; p < 0.01). However, the loss of GFR was much higher for the S-RALPN group after the surgery. (28.9 versus 18.4; p < 0.01). Importantly, patients had similar postoperative survival time between the two groups (p = 0.42; HR = 0.27). Conclusion P-RALPN is a safe and feasible surgery in the treatment of patients with complex renal tumors, which provides a new operative approach for clinicians to treat these patients.